ASUPAN KARBOHIDRAT, ASUPAN SERAT, DAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS TIPE II DI RSUD RATU ZALECHA MARTAPURA - Ratna Ratna; Laila Sholehah (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2026)
Type II Diabetes Mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin function. One of the factors affecting blood glucose levels is dietary intake, particularly carbohydrate and fiber intake. This study aimed to analyze the relationship between carbohydrate intake, fiber intake, and blood glucose levels in patients with Type II Diabetes Mellitus at RSUD Ratu Zalecha Martapura. This study used an analytic observational design with a cross-sectional approach. The sample consisted of 33 respondents selected using purposive sampling technique. Data on carbohydrate and fiber intake were collected using a 24-hour food recall, while fasting blood glucose data were obtained from laboratory examination results or medical records. Data were analyzed using the Chi-Square test with a significance level of α=0.05. The results showed that most respondents had excessive carbohydrate intake (39.4%), low fiber intake (90.9%), and uncontrolled fasting blood glucose levels (72.7%). There was a significant relationship between carbohydrate intake and fasting blood glucose levels (p<0.001), as well as between fiber intake and fasting blood glucose levels (p=0.003). Proper carbohydrate intake regulation and increased fiber consumption are important in controlling blood glucose levels in patients with Type II Diabetes Mellitus.